Reservoir Structure and Remaining Oil Distribution of Meandering River Channels: A Case Study of the Y92-1 Layer in the Jingbian Oilfield, Ordos Basin - Chun-ling Guo; Guo-min Fu; Jian-Chao Liu; Yang Wang; Yu-feng Wu; Cheng-wen Liu; Long-jun Wang; Li Qiao (Geofluids)
The majority of the Jurassic Yan’an Formation reservoirs in the Jingbian Oilfield of the Ordos Basin have entered the middle and late stages of development, and fine characterization of reservoir heterogeneity and recognition of the remaining oil distribution are the keys to formulating comprehensive adjustment for production. The Y92-1 layer of the Yan’an Formation Y9 reservoir in the LZ area of Jingbian Oilfield is taken as the research object in this paper. Based on logging data, core, and other basic data, the reservoir morphology in the study area is finely characterized. Single-channel units are subdivided, and the reservoir configurations of different hierarchical levels are analyzed qualitatively and quantitatively. Finally, combined with the plane profile consistency analysis of the morphological characteristics of the sand body in layer Y92-1 and the injection production mode, it is concluded that there may be four distribution patterns of the remaining oil in the study area, and the composite river channel sand body dominated by the lateral superimposed mode under the inverse lateral accretion shale bed tendency injection condition is a favorable enrichment area for the remaining oil. This mode is mainly distributed in the boundary part of the different periods of single sand body superposition. These understandings not only deepen the significance of tapping the potential of the remaining oil in frequently rerouted meandering rivers but also could provide effective guidance for the further remaining oil tapping.